2004
DOI: 10.1212/01.wnl.0000144282.42222.da
|View full text |Cite
|
Sign up to set email alerts
|

Association of cholesterol with stroke risk varies in stroke subtypes and patient subgroups

Abstract: Higher total and lower HDL cholesterol levels were associated with increased risk of ischemic stroke, especially certain stroke subtypes and patient subgroups. The lowest levels of total cholesterol were associated with an increased risk of all hemorrhagic strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
226
4
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(255 citation statements)
references
References 52 publications
19
226
4
6
Order By: Relevance
“…Okumara et al [17], Irribarren [18], Tirschwell [19], in their studies observed that hypercholesterolemia is a protective factor against ICH and that low blood cholesterol increases risk for ICH with an inverse relationship existing between serum cholesterol and incidence of ICH. Bang et al [20], postulated that Cholesterol is known to have effects on the vasculature and is essential for normal membrane fluidity, and adequate cholesterol levels may be important for maintaining the integrity of vessels and their resistance to rupture.…”
Section: Discussionmentioning
confidence: 98%
“…Okumara et al [17], Irribarren [18], Tirschwell [19], in their studies observed that hypercholesterolemia is a protective factor against ICH and that low blood cholesterol increases risk for ICH with an inverse relationship existing between serum cholesterol and incidence of ICH. Bang et al [20], postulated that Cholesterol is known to have effects on the vasculature and is essential for normal membrane fluidity, and adequate cholesterol levels may be important for maintaining the integrity of vessels and their resistance to rupture.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have thus reported a beneficial effect of LA on blood lipids and blood pressure 23, 24. Since hypercholesterolemia and hypertension have a different impact on the large precerebral arteries and the small cerebral arteries,9, 25, 26 this could partly explain the observed differences in risk between subtypes of ischemic stroke. We found a lower risk of large artery atherosclerosis and indications of a negative association between LA content in adipose tissue and small‐vessel occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that have addressed the limitations of prior studies generally have shown an association of elevated serum triglycerides, total cholesterol, low-density lipoprotein cholesterol, and nonhigh-density lipoprotein cholesterol with ischemic stroke risk, especially atherosclerotic and lacunar stroke subtypes. For instance, in 1 study the highest total cholesterol quintile was related to greater ischemic stroke risk vs the lowest quintile (odds ratio, 1.6; 95% confidence interval, 1.3 to 2.0), and the most robust subtype associations were for atherosclerotic stroke (OR, 3.2) and lacunar stroke (OR, 2.4) [34]. Elevated high-density lipoprotein cholesterol was shown to be protective for stroke in NOMASS [4].…”
Section: Modifiable Medical Risk Factorsmentioning
confidence: 93%